Ophichthus johnmccoskeri sp. nov. (Anguilliformes: Ophichthidae): a new snake eel from Indian waters, Bay of Bengal - Mohapatra, Anil; Ray, Dipanjan; Mohanty, Swarup R.; Mishra, Subhrendu Sekhar (Zootaxa, 2018)
A new species of snake eel (Anguilliformes: Ophichthidae: Ophichthinae), Ophichthus johnmccoskeri sp. nov., is described from three specimens collected from the northern part of the Bay of Bengal, India. Ophichthus johnmccoskeri sp. nov. is distinguished from its congeners by having the dorsal-fin origin well behind the pectoral-fin tips, by tooth pattern (lower jaw with a single row anteriorly followed by biserial teeth on anterior sides and tri-serial teeth posteriorly), and vertebral count (24 predorsal, 51–52 preanal, and 156–158 total).The new species has a single barbel between the anterior and posterior nostrils; vomerine teeth biserial anteriorly, multi to triserial and biserial medially and in a single row posteriorly; maxillary teeth biserial anteriorly and triserial posteriorly; tip of the lower jaw toothless; and tail length 1.6 times in total length.